Book Review: Artificial Intelligence Applications for Improved Software Engineering Development: New Prospects by Farid Meziane and Sunil Vadera. (15th December 2010) - Lopez-Cuadrado, Jose Luis; Colomo-Palacios, Ricardo; Gonzalez-Carrasco, Israel; Garcia-Crespo, Angel
Artificial Intelligence Applications for Improved Software Engineering Development: New Prospects, by Farid Meziane and Sunil Vadera. Hershey, PA, IGI Global, 2010. 370pp. ISBN: 1605667587